Six impossible things - Wood, Fiona (Fiona Anna) (New York ; Boston : Little, Brown and Company, 2015)
Fourteen-year-old Dan Cereill's life is turned upside-down when his father announces he is gay and leaves Dan and his mother with nothing, forcing them to move to an aunt's house, Dan to enroll in public school, and his mother to try to start a business, but the top thing on Dan's list is kissing Estelle, the girl next door.
"Poppy."
"First published in 2010 by Pan Macmilan Australia Pty, Ltd."--Title page verso.
Keywords: Moving, Household -- Juvenile fiction; Family problems -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Gay fathers -- Juvenile fiction; Australia -- Juvenile fiction; Moving, Household -- Fiction; Family problems -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Gay fathers -- Fiction; Australia -- Fiction